A newborn with ambiguous genitalia and persistent hypoglycemia - Salleh, Muhammad Farhan; Lai, Yin Ye; Mohamed Mokhtar, Normaizuwana; Thambiah, Subashini C.; Samsudin, Intan Nureslyna (SAGE Publications Inc., 2024)
Educational Objectives: In patients with classical 21-hydroxylase deficiency, the metabolic block in aldosterone and cortisol synthe-sis results in raised hormone precursor, 17-hydroxyprogesterone. Infants with simple virilizing congenital adrenal hyperplasia do not produce cortisol efficiently; however, they can synthesize adequate aldosterone to maintain salt-water balance.